Peer Observation, Reflection, and Expert Feedback: Pre-Service EFL Teachers’ Online Teaching Vocabulary to Young Learners - Mahboubeh Taghizadeh; Soraya Zafarpour (Iranian Journal of Applied Language Studies, 2022)
The objective was threefold: (a) to investigate the difference among online teaching performance of EFL student teachers at Iran University of Science and Technology who received peer feedback, expert feedback, and reflected on their own teaching practice; (b) to examine the difference between rating scores given by student teachers and those by instructor to online teaching; and (c) to determine student teachers’ best experiences, challenges, and lessons they learnt from expert feedback, peer observation, and reflection. The results of this mixed methods experimental research revealed no statistically significant difference in the three group’s scores on their second teaching practice; however, there was statistically significant difference between the scores of the first and second practices for all three groups. The results also showed that student teachers mostly underrated their first teaching, while they overrated their second teaching. The findings also indicated that their best experiences were related to using technological tools, working with Adobe Connect, making interesting materials, and using games and songs. Their challenges included lack of face-to-face communication, engaging all participants, and preparing suitable materials, whereas teaching new vocabulary in context, simplifying songs by pre-teaching their unknown words, and using online games and websites were the lessons they learnt.